Upaya Meningkatkan Kemampuan Siswa dalam Membedakan Barisan Aritmetika dan Geometri Melalui Penguatan Konsep Dasar dan Latihan Soal Relevan - Kairuddin; Indri Flora Br Ginting; Najwa Dwi Heryanti; Kristiani Siagian; Jhelsi Damanik; Gazla Hilmia Yunanda Rangkuti (STKIP Subang, 2026)
This study aims to examine students’ difficulties in distinguishing between arithmetic and geometric sequences, which are not only caused by limited computational skills but also by weak conceptual understanding of numerical patterns. Many students tend to memorize formulas without truly understanding the meaning of constant differences and constant ratios, leading to errors when identifying sequence types in various problem formats. This research employed a descriptive qualitative approach through teacher interviews and classroom observations at SMAS YPK Medan. The findings reveal that strengthening basic concepts through real-life contexts, combined with relevant and structured practice problems, significantly improves students’ ability to recognize and differentiate arithmetic and geometric patterns. These results emphasize that effective mathematics learning should focus on developing conceptual understanding and reflective thinking skills rather than merely procedural mastery.